Mechanisms of Budgeting on Public Service Obligation And Premium Subsidy in Agricultural Insurance - Abidin, M. Zainul (Badan kebijakan Fiskal, 2015)
This study aims to determine the mechanism of funding the assignment (Public Service Obligation/PSO) to State Owner Enterprises and mechanism of budgeting for the provision premium payment of agricultural insurance. This research uses descriptive qualitative method. The process of analysis is performed using the laws, the theory of public finance, and insurance. Collecting data in this study using a literature study. The result of research shows that the assignment of agricultural insurance and the provision of premium payments are two separate programs and each requires its own funding proposal. Budget mechanisms to implement agricultural insurance assignment and assistance insurance premiums is guided by the Law 17/2003 and Government Regulation 90/2010. Proposed activities should be included in the Work Plan and Budget of the Ministry of Agriculture as technical ministries and proposed into the Draft State Budget. Furthermore, the budget allocation in the budget document's of the Ministry of Agriculture implemented in accordance with the statutory provisions pertaining to the procedures for budget execution. The assignment of agricultural insurance mechanisms implemented under Law 19/2003 and Government Regulation 45/2005. The payment mechanism at the expense of the state budget for the payment of a premium subsidy based on the Government Regulation 45/2013.